Extracorporeal Membrane Oxygenation for COVID-19 Respiratory Distress Syndrome: An Italian Society for Cardiac Surgery Report. Issue 4 (18th January 2021) - Loforte, Antonio; Di Mauro, Michele; Pellegrini, Carlo; Monterosso, Christian; Pelenghi, Stefano; Degani, Antonella; Rinaldi, Mauro; Cura Stura, Erik; Sales, Gabriele; Montrucchio, Giorgia; Mangino, Domenico; Terrini, Alberto; et al.
Abstract : An increased need of extracorporeal membrane oxygenation (ECMO) support is going to become evident as treatment of SARS-CoV-2 respiratory distress syndrome. This is the first report of the Italian Society for Cardiac Surgery (SICCH) on preliminary experience with COVID-19 patients receiving ECMO support. Data from 12 Italian hospitals participating in SICCH were retrospectively analyzed. Between March 1 and September 15, 2020, a veno-venous (VV) ECMO system was installed in 67 patients (94%) and a veno-arterio-venous ECMO in four (6%). Five patients required VA ECMO after initial weaning from VV ECMO. Thirty (42.2%) patients were weaned from ECMO, while 39 (54.9%) died on ECMO, and six (8.5%) died after ECMO removal. Overall hospital survival was 36.6% (n = 26). Main causes of death were multiple organ failure (n = 14, 31.1%) and sepsis (n = 11, 24.4%). On multivariable analysis, predictors of death while on ECMO support were older age ( p = 0.048), elevated pre-ECMO C-reactive protein level ( p = 0.048), higher positive end-expiratory pressure on ventilator ( p = 0.036) and lower lung compliance ( p = 0.032). If the conservative treatment is not effective, ECMO support might be considered as life-saving rescue therapy for COVID-19 refractory respiratory failure. However warm caution and thoughtful approaches for timely detection and treatment should be taken for such a delicate patients population.